1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Using the generalized triangle inequality

  1. Nov 3, 2012 #1
    1. The problem statement, all variables and given/known data
    Using the generalized triangle inequality, prove |d(x,y) - d(z,w)| ≤ d(x,z) + d(y,w)

    2. Relevant equations
    d(x,y) is a metric
    triangle inequality: d(x,y) ≤ d(x,z) + d(z,y)

    3. The attempt at a solution
    I know that this needs to be proved with cases: a) d(x,y) - d(z,w) ≥ 0, and b) d(x,y) - d(z,w) < 0. I know that for case a), we have |d(x,y) - d(z,w)| = d(x,y) - d(z,w). The part I am stuck at is that by applying the generalized triangle inequality to this expression, we are supposed to get d(x,y) - d(z,w) ≤ d(x,z) + d(w,y). I just do not understand why. Can anyone help please?
  2. jcsd
  3. Nov 3, 2012 #2
    Why would this prove anything?? Why do you even think (a) and (b) are true?
  4. Nov 3, 2012 #3
    OK, I used the two cases a) d(x,y) - d(z,w) ≥ 0 and b) d(x,y) - d(z,w) < 0 because of the absolute value in the problem. So for case a) i need to prove d(x,y) - d(z,w) ≤ d(x,z) + d(y,w) and for case b) i need to prove d(z,w) - d(x,y) ≤ d(x,z) + d(y,w)
  5. Nov 3, 2012 #4
    OK, that makes sense.

    So you need to prove d(x,y)-d(z,w) ≤ d(x,z) + d(y,w). What happens if you add d(z,w) to both sides?
  6. Nov 3, 2012 #5
    Ok, so then adding d(z,w) to both sides gives d(x,y) ≤ d(x,z) + d(y,w) + d(z,w), so d(x,z) + d(z,w) + d(y,w) ≥ d(x,w) + d(w,y) by the triangle inequality, and d(x,w) + d(w,y) ≥ d(x,y) by the triangle inequality, so d(x,y) ≤ d(x,z) + d(y,w) + d(z,w). Thanks so much, now I understand where this is coming from!
  7. Nov 3, 2012 #6
    Note: if you actually write up the proof then you have to reverse it. You can't write: from [itex]d(x,y)-d(z,w) \leq d(x,z) + d(y,w)[/itex] follows [itex]d(x,y)\leq d(x,z)+d(y,w)+d(w,z)[/itex]. This is true, but it isn't helpful since you started with what you wanted to proof.

    What you have to do is write: from [itex]d(x,y)\leq d(x,z)+d(y,w)+d(w,z)[/itex] follows [itex]d(x,y)-d(z,w) \leq d(x,z) + d(y,w)[/itex].
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook